Prevalence of high time and its correlates among 3 to 10 years school going children during COVID-19 pandemic in Bhaktapur district. - Shrestha, Rajan (2021)
Summary: The use of digital screens has been increased in all over the world. The long use of these screens has adverse effect on physical, mental, social well-being of the children. Nowadays, children start using screen from their early childhood which has increased due to the availability, and the change in teaching learning activities from classroom teaching to online teaching due to COVID-19 pandemic. Though the screen using time has estimated to be high, there is paucity of information on the burden of high screen among school going children. So, explored its prevalence and correlates among children from 3-10 years of age during COVID-19 pandemic using cross sectional descriptive study. The data was collected from 630 household children from 21 wards (cluster) from 2011 Census from two randomly selected municipalities of Bhaktapur district, interviewing their parents as proxy respondent, in the month of April 2021 when children were taking physical classes. The data was collected using a questionnaire developed. Perception related questions were developed in 5-point Likert's scale. The collected data was entered in EpiData 3.1 and analyzed using R programming. Among the participants, almost equal number of boys and girls participated with mean (SD) age 7.01(2.18) years. About ¾ participants (n=468, 74.3) were from private schools. Only very few participants were having online classes (n=24, 3.8%) while most of them were having physical classes (n=96.2%). The prevalence of high screen time among the participants was found very high (67%, 95% CI=63.8%-71.3%), which is even higher in boys (74.1%, 95% CI=68.9%-78.9%). The mean (SD) daily screen used time by participants was 2.78 (2.08) hours, even higher among boys (3.24 (2.34)) than girls (2.32(1.67)). The median screen use time before COVID-19 pandemic was 1.00 hour which was increaed to 2.25 hours. Screen use time during COVID-19 pandemic (Mean Rank=275.77) is significantly increased (p<0.001) than before the pandemic (Man Rank=116.60). The digital screen most of the participants had was Smartphone (n=604,95.9%) followed by Television (n=464, 73.7%). Most of the participants used the screens for playing games (n=562, 89.0%). The most perceived adverse effect the children had was eye problem (n=548, 87.0%). The mean (SD) perceived score on digital screen entertaining for children was 4.05 (0.77), the mean (SD) score in confidence they have in controlling the children's screen use score was 2.84(1.05). Participants going to private school were about 2 times (AOR=2.25, 95% CI=1.31-3.84) more likely to have high screen time than those going to public school. Participant using screens for playing games were about 3 times (AOR=3.30, 95% CI=1.59-6.85) more likely to have high screen time than those not playing games. The parents who used to scold their children not to use screen were about 3 times (AOR=3.33, 95% CI=1.97-5.65) more likely to have high screen time than who do not scold. About two in three school going children have high screen time. Conduction of awareness programs through the stakeholders to reduce screen time and adverse health effects is recommended. Studies to find out the effective strategies to reduce screen time is also recommended.